A Bibliometric Analysis of Physical Literacy Studies in Relation to Health of Children and Adolescents - Javier Urbano-Mairena; Antonio Castillo-Paredes; Laura Muñoz-Bermejo; Ángel Denche-Zamorano; Jorge Rojo-Ramos; Raquel Pastor-Cisneros; María Mendoza-Muñoz (MDPI AG, 2023)
Regular physical activity (PA) is an essential component of maintaining good health, thereby improving the physical and psychological well-being of the population. PA performed during childhood and adolescence can have repercussions in adulthood, contributing to the prevention of chronic activities and improving quality of life. Given its high relationship with PA, physical literacy could play a crucial role in valuing and participating in a physically active lifestyle, thus addressing low rates of PA participation from an early age. This bibliometric analysis provides a globalized view of physical literacy (PL) and its relationship with health, pathologies, prevention, or intervention among children and adolescents. Publications registered on Web of Science were analyzed using bibliometrics based on data from 141 documents published between 2014 and 2022, while the VOSviewer software v. 1.6.18. was used for the processing and visualization of the data and metadata. The results show an exponential growth in scientific research over the last 8 years, with an accumulation of documents in four journals and a distribution of publications spanning thirty-seven countries and regions. The network of researchers consists of 500 researchers, with the largest number of publications corresponding to 18 co-authors with at least 5 publications. The principal purpose of this research was to identify the most prolific co-authors, most-cited journals and co-authors, and the most relevant keywords.